Ceruloplasmin inhibits the proliferation, migration and invasion of nasopharyngeal carcinoma cells and is negatively regulated by miR-543. (7th July 2022) - Yang, Hang; Bao, Yangyang; Jin, Fenfen; Jiang, Chonghan; Wei, Zhanhui; Liu, Zhenli; Xu, Yaping
Abstract: Background: Ceruloplasmin (CP), recognized as a member of multicopper oxidase family, is related to the progression of diverse cancers in human beings. This study is designed to clarify the expression characteristics, biological function and related mechanism of CP in nasopharyngeal carcinoma (NPC). Methods: CP expression in NPC tissues and cells was probed by quantitative real-time polymerase chain reaction (qRT-PCR), immunohistochemistry (IHC) and Western blot. After gain-of-function and loss-of-function models were established, cell counting kit-8 (CCK-8), Transwell and BrdU assays were employed to measure cell viability, migration and invasion. The targeting relationship between microRNA-543 (miR-543) and CP was verified by dual-luciferase reporter gene assay. Results: As against normal nasopharyngeal epithelial tissues, CP expression was significantly lower in NPC tissues, which was associated with higher clinical stage and the short overall survival time. Compared with the control group, CP overexpression markedly restrained the growth, migration and invasion of NPC cells; knocking down CP had the opposite effect. MiR-543 directly targeted CP and negatively modulated its expression. Conclusion: CP restrains the growth, migration and invasion of NPC cells and is negatively regulated by miR-543.